A lot size inventory model for the Weibull distributed deterioration rate with discounted selling price and stock-dependent demand. (29th July 2009) - Shah, Nita H.; Shah, Bhavin J.; Wee, H.M.
In this paper, we present an inventory model with stock-dependent demand and deteriorating inventory. It is assumed that the deterioration rate follows a three-parameter Weibull distribution. The strategy of offering discounts in the selling price to boost demand is studied. The optimal discount in the selling price to maximise profit and the effects of deterioration on the optimal solution are the foci of this study. A numerical example and sensitivity analysis are carried out to validate the theory.